Driving Factors Influencing Watershed Management and Sustainability: A Systematic Review - Taslim, Ivan; Basuni, Sambas; Purwanto, Moh. Yanuar Jarwadi; Santikayasa, I Putu (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2025)
Watershed management and sustainability have gained significant global attention due to escalating environmental, socioeconomic, and governance challenges. This study presents a Systematic Literature Review (SLR) aimed at identifying and synthesizing key driving factors that influence watershed management and sustainability. A comprehensive search was conducted exclusively in the Scopus database, covering publications from 2013 to 2023. Through PRISMA-based screening and thematic analysis of 193 relevant studies, a total of 37 driving factors were identified. These factors were classified into three main domains: biophysical (7 factors), socio-economic (13 factors), and institutional (17 factors). The findings reveal that institutional factors are most prominently emphasized, followed by socio economic and biophysical dimensions. This synthesis provides a holistic understanding of the complex and interconnected elements that drive watershed sustainability. The insights derived are intended to inform future research, support evidence-based policymaking, and strengthen integrated watershed management practices across diverse geographic and socio-political contexts. The search employed multiple keyword combinations, including ”watershed”, ”catchment”, ”river basin”, ”drivers”, ”influencing factors”, and ”determinants”, ensuring broader thematic coverage within the Scopus database.